Análisis de la responsabilidad social empresarial del centro comercial “Portal del Quindío” con sus clientes, empleados y directivos. (2013)
Globalization and free market made Social Responsibility (CSR) is in those companies are leaders not only recognized for their social responsibility, but also their responsibility to the environment, economy and community. The same globalization has made strategies Centers that benefit not only their business but the environment in which it is surrounded, the society. Therefore, it was raised to identify targets of interest groups “Quindío Portal”; CSR goals set assuming the Portal of Quindío with its stakeholders, and determine responsibility and propose strategies that contribute to the improvement of Portal del Quindío with its stakeholders. It took into account theoretical support, the origin and concept of CSR, business ethics, its stakeholders, practices and environmental responsibility.